Faktor menyumbang kepada penagihan relaps dalam kalangan penagih dadah PUSPEN di Semenanjung Malaysia - Ibrahim, Fauziah; Abu Samah, Bahaman; Abu Talib, Mansor; Sabran, Mohammad Shatar (Agensi Antidadah Kebangsaan, 2009)
This study was conducted to examine the influence of three main factors, which are individual, social environmental and rehabilitation program effectiveness on the incidence of drug addict on relapse. Self-administered questionnaires were used to gather data. Data collected were analysed using “SPSS for Windows”. The sample consisted of 400 drug addict on relapse cases which were selected through the method stratified random sampling and systematic random sampling from eight Rehabilitation Centers throughout Peninsular Malaysia. Research Instruments were developed and adopted from various sources. The quantitative data were analyzed using multiple regression analysis (stepwise). The findings indicated that three predictive variables: self-confidence (Beta=.743), support from society (Beta=.155) and family support (Beta=.086) with the total of 65.3% as the most influencing factors contributed to drug addict on relapse.